2013
DOI: 10.1159/000346475
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Ki67 and Breast Cancer Prognosis

Abstract: Background: Ki67 is an immunohistochemical proliferation marker in many types of cancer and has been widely studied among breast cancer patients mostly through retrospective studies. Methods: The MEDLINE/PubMed database was searched for publications with the medical subject heading ‘Ki 67’ and the key words ‘breast’, ‘cancer’, and ‘prognosis’. We restricted our search to articles published until 2012. Results: In this review, we included 78 articles and abstracts that were accessible and available in English. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
83
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(94 citation statements)
references
References 136 publications
8
83
1
1
Order By: Relevance
“…The present population-based study revealed that Ki67 was significantly associated with all the clinicopathological parameters, with the exception of age. In accordance with previous studies, the present study confirmed the importance of the Ki67 level in predicting the prognosis of BC (23)(24)(25)(26).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present population-based study revealed that Ki67 was significantly associated with all the clinicopathological parameters, with the exception of age. In accordance with previous studies, the present study confirmed the importance of the Ki67 level in predicting the prognosis of BC (23)(24)(25)(26).…”
Section: Discussionsupporting
confidence: 93%
“…Ki67 is a proliferation marker that is expressed in all the phases of the cell cycle, with the exception of the G 0 phase (2)(3)(4). A number of studies have demonstrated the prognostic value of Ki67 in BC (5,6). In addition, Ki67 levels are useful in identifying patients that are most likely to benefit from chemotherapy (7).…”
Section: Introductionmentioning
confidence: 99%
“…ER status has been largely identified as being inversely correlated with Ki-67, with the higher rates of ER positivity shown in the lowest proliferating tumors 21 . Moreover, it could be demonstrated that high levels of Ki-67 are associated with HER2/-neu positivity according to former studies.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated the primary role of proliferation signatures in breast cancer and most of them support the prognostic value of Ki67. 5,6 For example, a gene expression-based intrinsic subtype classification of breast cancers with pathological features found that a Ki67 score $14% distinguished luminal B from luminal A. 7 This was subsequently supported by the…”
Section: Introductionmentioning
confidence: 91%